Students' perception of the effectiveness of highly rated tertiary instructors - Entao-Limson, Elisa Bernadette (2011)
This qualitative study explored the effectiveness of highly rated instructors as perceived by the students. The central phenomenon addressed in this study revolved on the characteristics and teaching effectiveness of the highly rated instructors, and the classroom experiences and self-improvements of their students. Focused group discussions were conducted among the group of students. Results reveal that the effective teachers possess favorable traits, pedagogical knowledge and content in their classroom teaching. Their effectiveness and the classroom experiences they provide to students were also found to be linked to their characteristics. Findings also that the students' classroom experiences were mostly positive and negative and that students reported to have improved resulting from the instructors' effectiveness.
Keywords: Effective teaching; College teachers; Teacher effectiveness; Teacher evaluation; Model teacher